THE EFFECTIVENESS OF STAD AND TGT TO ENHANCE NARRATIVE TEXT READING COMPREHENSION OF THE STUDENTS WITH HIGH AND LOW ACHIEVEMENT (Universitas Negeri Semarang, 2015)
This study investigated the effectiveness of STAD and TGT for enhancing narrative text reading comprehension of the students with high and low achievement. This study was a quantitative research, using an experimental factorial design 2x2. The participants of this study were 71 students of the eighth graders of State Islamic Junior High School Lebaksiu. Thestudents were divided into two groups, experimental group and controlgroup. The students of experimental group wasgiven STAD in learning narrative text reading comprehension and thecontrol group wasgiven TGT inlearning narrative text reading comprehension.The findings of this study showedthat STAD and TGT have significant effect for enhancing narrative text reading comprehension. However, the techniquesgiven for enhancing narrative text reading comprehension and student’s achievement did not have any interactions